Processo de aceleração: os impactos do programa SEED nas startups e seus determinantes - Luís Henrique Dos Santos Figueiredo (2018)
The startup accelerator is a rapidly expanding phenomenon that emerged from the 2000s, based on the digital economy and the emergence of new areas of science interest. Its purpose is to promote the rapid and successful creation of technology-based companies by providing specific services, focusing on entrepreneurship education and mentoring during an intensive and timelimited program. This study presents the impacts of the acceleration process developed by SEED - Startups and Entrepreneurship Ecosystem Development, a program that applies public resources to promote business projects in the state of Minas Gerais with the aim of developing its ecosystem of entrepreneurship and innovation. The research interviewed twenty-five startup founders graduated by SEED’s program between 2014 and 2016. The study presents a specificpurpose methodology for measuring the impacts of accelerators and an explanatory logic model of determinant factors of startup’s growth using crisp-set QCA analysis. The Qualitative Comparative Analyses (QCA) was the methodological approach used to investigate the parcimonious solutions that explain the results of interest. The most parcimonious solutions produced by the logic model provided a tool do link the configurations of causal conditions – the accelerators’ process practices - to the startups’s economic growth, based on the entrepreneurs’ evaluation about the impacts of SEED’s program on their performance.